Using a Prediction Model to Manage Cyber Security Threats - Venkatesh Jaganathan; Priyesh Cherurveettil; Premapriya Muthu Sivashanmugam (The Scientific World Journal)
Cyber-attacks are an important issue faced by all organizations. Securing information systems is critical. Organizations should be able to understand the ecosystem and predict attacks. Predicting attacks quantitatively should be part of risk management. The cost impact due to worms, viruses, or other malicious software is significant. This paper proposes a mathematical model to predict the impact of an attack based on significant factors that influence cyber security. This model also considers the environmental information required. It is generalized and can be customized to the needs of the individual organization.